2016
DOI: 10.1016/j.cub.2015.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Moonlight Drives Ocean-Scale Mass Vertical Migration of Zooplankton during the Arctic Winter

Abstract: In extreme high-latitude marine environments that are without solar illumination in winter, light-mediated patterns of biological migration have historically been considered non-existent [1]. However, diel vertical migration (DVM) of zooplankton has been shown to occur even during the darkest part of the polar night, when illumination levels are exceptionally low [2, 3]. This paradox is, as yet, unexplained. Here, we present evidence of an unexpected uniform behavior across the entire Arctic, in fjord, shelf, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
155
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 47 publications
8
155
0
Order By: Relevance
“…The classical paradigm of biological quiescence during the Arctic polar night, has been challenged by a series of works recently published concerning feeding hyperiid amphipods during Arctic-darkness (Kraft et al, 2013), mass-vertical zooplankton migration during Arctic winter driven by moonlight (Last et al, 2016), and unexpected levels of biological activity during the polar night (Berge et al, 2015). Berge et al (2009) showed that diel vertical migration during the Arctic winter is an important feature of the zooplankton community, especially for copepods in the epipelagial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical paradigm of biological quiescence during the Arctic polar night, has been challenged by a series of works recently published concerning feeding hyperiid amphipods during Arctic-darkness (Kraft et al, 2013), mass-vertical zooplankton migration during Arctic winter driven by moonlight (Last et al, 2016), and unexpected levels of biological activity during the polar night (Berge et al, 2015). Berge et al (2009) showed that diel vertical migration during the Arctic winter is an important feature of the zooplankton community, especially for copepods in the epipelagial.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline information regarding physical, chemical, and biological conditions is lacking for many parts of the Arctic (Wassmann and Reigstad, 2011; and crucial information on processes, species interactions, and behaviorial patterns recently uncovered (Berge et al, 2009(Berge et al, , 2014(Berge et al, , 2015Kraft et al, 2013;Last et al, 2016), suggests that current knowledge of the high Arctic marine ecosystem is incomplete. Thus, our understanding of the susceptibility of the Arctic ecosystem to a warmer ocean climate is limited and pathways along which changes will proceed are uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronin et al, 2016), that can be particularly important during the Arctic winter. Recently published work from this region show that some organisms respond to even very weak variations in light level, and mass-vertical migration during Arctic winter driven by moonlight has been documented (Cohen et al, 2015;Last et al, 2016). However, these studies have focused on zooplankton in the upper 50 m.…”
Section: Introductionmentioning
confidence: 99%
“…Diel vertical migration (DVM) is a well-documented behavior among diverse taxa of zooplankton from tropical environments (TrE) [1][2][3] to higher latitude environments [4][5], and the adaptive significance of this behavior has been explained by a wide array of competing hypothesis [6]. The major driving factors of this behavior can be attributed to predator avoidance [7], prevention from light related mortality [8], the bioenergetic advantage [9], and demographic benefits [10].…”
Section: Introductionmentioning
confidence: 99%